Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1186/1747-1028-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Cullin-RING ubiquitin ligases: global regulation and activation cycles

Abstract: Cullin-RING ubiquitin ligases (CRLs) comprise the largest known category of ubiquitin ligases. CRLs regulate an extensive number of dynamic cellular processes, including multiple aspects of the cell cycle, transcription, signal transduction, and development. CRLs are multisubunit complexes composed of a cullin, RING H2 finger protein, a variable substrate-recognition subunit (SRS), and for most CRLs, an adaptor that links the SRS to the complex. Eukaryotic species contain multiple cullins, with five major type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
319
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(324 citation statements)
references
References 131 publications
4
319
1
Order By: Relevance
“…Nedd8 deconjugation is catalyzed by the COP9 signalosome (CSN). Strikingly, the paradox observed for Cand1 is also evident for CSN, because CSN clearly functions as a negative regulator of SCF in vitro, yet genetic data suggest a positive role for SCF activity in vivo [5]. A prevailing model has been that SCF and other CRLs must undergo neddylation cycles whereby deneddylated cullins are sequestered by Cand1, allowing substrate receptor exchange followed by reactivation of the assembled CRL by neddylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nedd8 deconjugation is catalyzed by the COP9 signalosome (CSN). Strikingly, the paradox observed for Cand1 is also evident for CSN, because CSN clearly functions as a negative regulator of SCF in vitro, yet genetic data suggest a positive role for SCF activity in vivo [5]. A prevailing model has been that SCF and other CRLs must undergo neddylation cycles whereby deneddylated cullins are sequestered by Cand1, allowing substrate receptor exchange followed by reactivation of the assembled CRL by neddylation.…”
mentioning
confidence: 99%
“…However, its true function was somewhat of a mystery. Cand1 acted as a potent SCF inhibitor in vitro by displacing the FboxP-Skp1 pair from Cul1, but genetic experiments classified Cand1 as a positive regulator of SCF and other CRLs in vivo [5]. An additional layer of complexity is added by covalent modification of cullins with the ubiquitin-like protein Nedd8.…”
mentioning
confidence: 99%
“…It has previously been shown that this can be mediated by interaction between substrate proteins and BTB domain-containing subunits of the ubiquitin ligase complexes (Bosu and Kipreos 2008;Hotton and Callis 2008;Petroski and Deshaies 2005;Sumara et al 2008). However, our results indicate that recruitment can also occur by interaction between PEST sequences in a substrate protein, in this case HSF2, and the Cul3 subunit of the Cul3-RING ligase complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Cul3, a member of the Cullin family of proteins, is a subunit of a Cullin-RING ubiquitin E3 ligase complex that polyubiquitinates many important proteins, leading to their degradation by the proteasome (Bosu and Kipreos 2008;Hotton and Callis 2008;Petroski and Deshaies 2005;Sumara et al 2008). Cul3-containing ubiquitin ligases have been found to play important roles in the regulation of mitosis, development, cytoskeletal proteins, and transcription factors (Pintard et al 2004;Sumara et al 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…NEDD8 is a ubiquitin-like protein that is covalently attached to its substrates. Cullins form the largest class of NEDD8 substrates, and attachment of NEDD8 to cullins activates their associated E3 ubiquitin ligase activity and thus promotes polyubiquitination and proteasomal degradation of target proteins (28). The identification of these two genes whose functions converge on the polyubiquitination and proteasomal degradation pathway led us to hypothesize that SYVN1 and NEDD8 promote ⌬F508-CFTR polyubiquitination and that depleting either protein would improve ⌬F508-CFTR maturation in CF cells.…”
Section: Rna Interference Screen Of 13 Candidates Reveals Role For Symentioning
confidence: 99%